Synthesis and Biological Evaluation of 1,3,4-Oxadiazole Fused Resveratrol Derivatives as Anticancer Agents - Naresh, Vema Venkata; Kumari, Y. Bharathi; Sridhar, Mussulla; Raju, Addada Ramakrishnam; Rao, A. Srinivasa (Asian Journal of Chemistry, 2020)
A novel target compounds (9a-j) were design and synthesized and characterized by 1H & 13C NMR, ESI-MS spectral analysis. Further, these were tested for their anticancer activity against three human cancer cell lines such as MCF-7, MDA MB-231 (breast), A549 (Lung) and adriamycin was used as positive control. Among ten compounds, two compounds like 9b and 9j were showed a significant anticancer activity compared to control drug.